1999
DOI: 10.1063/1.370829
|View full text |Cite
|
Sign up to set email alerts
|

Midgap density of states in hydrogenated polymorphous silicon

Abstract: When silicon thin films are deposited by plasma enhanced chemical vapor deposition in a plasma regime close to that of the formation of powder, a new type of material, named polymorphous silicon (pm-Si:H) is obtained. pmSi:H exhibits enhanced transport properties as compared to state-of-the-art hydrogenated amorphous silicon (a-Si:H). The study of space-charge-limited current in n+-i-n+ structures along with the use of the modulated photocurrent technique, of the constant photocurrent method and of steady-stat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

6
43
2

Year Published

2001
2001
2016
2016

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 96 publications
(51 citation statements)
references
References 15 publications
6
43
2
Order By: Relevance
“…Through spectroscopic ellipsometry, Rutherford Backscattering and ERDA measurements, it has been shown that pm-Si:H films are denser than a-Si:H films, in spite of their high hydrogen content, in the range of 15−20% [7]. The peculiar structure of pm-Si:H results in a low defect density (of the order of 10 14 cm −3 eV −1 at Fermi level as measured by SCLC and modulated photocurrent) and higher resistance to light-soaking than aSi:H [8][9][10]. In particular improved hole transport appears to be a key point for the application of this material in solar cells [11].…”
Section: Introductionmentioning
confidence: 99%
“…Through spectroscopic ellipsometry, Rutherford Backscattering and ERDA measurements, it has been shown that pm-Si:H films are denser than a-Si:H films, in spite of their high hydrogen content, in the range of 15−20% [7]. The peculiar structure of pm-Si:H results in a low defect density (of the order of 10 14 cm −3 eV −1 at Fermi level as measured by SCLC and modulated photocurrent) and higher resistance to light-soaking than aSi:H [8][9][10]. In particular improved hole transport appears to be a key point for the application of this material in solar cells [11].…”
Section: Introductionmentioning
confidence: 99%
“…Also used as the top cell in such structures is polymorphous silicon, a nanostructured material deposited by PECVD at high pressure and RF power, in a regime where silicon clusters and nanocrystals synthesized in the plasma contribute to the growth along with silicon radicals [9]. It has been reported in previous studies that pm-Si:H has better electronic properties and stability than conventional a-Si:H [10][11][12][13]. Moreover, the pm-Si:H optical gap being slightly larger than the a-Si:H one, the use of pm-Si:H in a tandem structure in place of a-Si:H allows one the possibility to increase the opencircuit voltage of the entire device and therefore to increase the electric output of the photovoltaic modules.…”
Section: Introductionmentioning
confidence: 99%
“…The stability of a-Si:H films is related to the amorphous network structure, whereas the improvement of amorphous network may finally lead to the formation of micro or nanocrystalline silicon (μc-or nc-Si), which shows no noticeable light-induced degradation, but a poor photosensitivity. It has been confirmed in recent years that hydrogenated silicon films deposited in the regime just above the phase transition from amorphous to crystalline state could gain both the fine photoelectronic properties like a-Si:H and high stability like μc-Si:H [1][2][3][4][5][6]. The demand of these applications is not only a high quality but also a high deposition rate on the preparation.…”
Section: Introductionmentioning
confidence: 99%